Full-term extrauterine abdominal pregnancy with healthy newborn: a case report and review of the literature - Bashir, Mohammed Elkhair; Alawad, Awad (International Journal of Medicine, 2014)
Abdominal pregnancy is a rare form of ectopic pregnancy with very high morbidity and mortality for both the mother and the fetus. Diagnosis and management can pose some difficulties especially in low-resource centers. High index of suspicion is vital in making prompt diagnosis in such situations. A case of abdominal pregnancy that resulted in a live healthy newborn at a Regional Hospital in Somalia is presented.